2019
DOI: 10.3389/fcell.2019.00109
|View full text |Cite
|
Sign up to set email alerts
|

Acylation – A New Means to Control Traffic Through the Golgi

Abstract: The Golgi is well known to act as center for modification and sorting of proteins for secretion and delivery to other organelles. A key sorting step occurs at the trans -Golgi network and is mediated by protein adapters. However, recent data indicate that sorting also occurs much earlier, at the cis -Golgi, and uses lipid acylation as a novel means to regulate anterograde flux. Here, we examine an emerging role of S-palmitoylation/acylation as a mechanism to regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 112 publications
0
22
0
Order By: Relevance
“…A recent review by Ernst et al (2019) demonstrated the importance of accounting for the spatial context of PATs, specifically PAT localization within distinct Golgi domains, to better understand anterograde sorting of specific substrates en route to the cell surface. With this in mind, we investigate in this review the possibility that PAT spatial context, or PAT subcellular localization, governs substrate targeting following substrate palmitoylation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by Ernst et al (2019) demonstrated the importance of accounting for the spatial context of PATs, specifically PAT localization within distinct Golgi domains, to better understand anterograde sorting of specific substrates en route to the cell surface. With this in mind, we investigate in this review the possibility that PAT spatial context, or PAT subcellular localization, governs substrate targeting following substrate palmitoylation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Our model is in agreement with the local S-palmitoylation described for substrates such as PSD95 at dendritic spines 38 and calnexin at the ER 47 , but adds the Golgi as a compartment in which PMPs can be locally modified and retained. To our knowledge, S-palmitoylation via the large number of Golgi-localized zDHHCs has been exclusively discussed in the context of Golgi-to-PM transport of integral 48 and PMPs 13 . We hereby challenge the current model and show instead that PMP localization to one compartment or another (including Golgi and PM) is not a consequence of sequential trafficking of the PMPs but rather a direct localization driven by the substrate-specific PAT activities at different compartments.…”
Section: Discussionmentioning
confidence: 99%
“…First, palmitoylated C186 decreases the interaction with GDI1, hence impairs extraction of the mutant from the membrane resulting in a more stable interaction with membranes. Second, replacement of R186 by palmitoylated C186 should affect the membrane preference of Cdc42, both by removing a positively charged residue that favors the recognition of negatively charged phosphatidylinositides that are enriched at the plasma membrane 23 and by adding a lipid known to support trafficking through the Golgi (for example: reviewed in 28 ). Thus, both contributions are likely to determine why the Cdc42 mutant appears mostly trapped at the Golgi.…”
Section: Discussionmentioning
confidence: 99%